Pious Followers of the Old Faith Near Opočka (Some Socio- and Ethnolinguistic Notes) - Афанасьевна Морозова, Надежда; Чекмонас, Валерий (Slavistica Vilnensis, 2002)
The Old Believers who live in the villages along the Issa River near the town of Opočka in the Pskov region belong to the radical branch of Orthodox Russian dissidents’, the so-called Fedoseyevian denomination. Unlike the majority of the Feodosiy’s followers, who over the 19–20 cc. gradually accepted the ideas of the non-priestist Pomorians, who areclosely related to them, the Old Believers near Opočka continue the “celibatarian” ideology. There is almost nothing known about the everyday life of these rural traditional Fedoseyevians. The tiny community we investigated consists of two parishes, and is currently on the brink of extinction. The main feature of the confessional structure of this community is the subdivision of its members into three groups, respectively, the rabskije, the newlyweds, navažonyje and the laypeople (or temporals mirskije). The status of each group within the community and the rules of conduct for its members are described on the basis of accounts recorded during the expedition.